2011
DOI: 10.1007/s11099-011-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chloroplast morphology of different parenchyma cells in leaves of Haberlea rhodopensis Friv. during desiccation and following rehydration

Abstract: The size, shape, and number of chloroplasts in the palisade and spongy parenchyma layers of Haberlea rhodopensis leaves changed significantly during desiccation and following rehydration. The chloroplasts became smaller and more rounded during desiccation, and aggregated in the middle of the cell. The size and number of chloroplasts in the palisade parenchyma cells were higher than in spongy parenchyma. The good correlation observed between the size or number of chloroplasts and the cross-sectional area of mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
2
3
1
Order By: Relevance
“…Hence, we suggest that the chloroplasts of seedlings under nurse plants move to maximize photosynthesis, because light coming through the canopy provided by nurse plants is weak, diffuse, and transient owing to the movement of the sun, as proposed by Park et al (1996) [50] for shade plants. Interestingly, seedlings under non-watering treatments, both in light and shade, showed higher chloroplast density, contrary to that described for other plants in which the number of chloroplasts decreases under water stress or when exposed to intense light [51] , [52] , [53] . This could be a mechanism used by O. streptacantha seedlings to maintain photosynthetic activity under stress conditions.…”
Section: Discussioncontrasting
confidence: 97%
“…Hence, we suggest that the chloroplasts of seedlings under nurse plants move to maximize photosynthesis, because light coming through the canopy provided by nurse plants is weak, diffuse, and transient owing to the movement of the sun, as proposed by Park et al (1996) [50] for shade plants. Interestingly, seedlings under non-watering treatments, both in light and shade, showed higher chloroplast density, contrary to that described for other plants in which the number of chloroplasts decreases under water stress or when exposed to intense light [51] , [52] , [53] . This could be a mechanism used by O. streptacantha seedlings to maintain photosynthetic activity under stress conditions.…”
Section: Discussioncontrasting
confidence: 97%
“…Therefore, in the present study, a greater thickness of mesophyll correlated with a greater thickness of palisade parenchyma in polymertreated plants. Nagy-Déri et al (2011) suggested that palisade parenchyma cells are more responsive to water availability than spongy cells, as observed in this study.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the RWC in R. nathaliae decreased from 98% to 7.8% during dehydration (Gashi et al, 2013). Kinetics of RWC during the dehydration-rehydration cycle were reported by other authors in R. serbica (Augusti et al, 2001;Quartacci et al, 2002;Sgherri et al, 2004;Veljovic-Jovanoviç et al, 2006) and H. rhodopensis (Djilianov et al, 2011;Georgieva et al, 2010;Mihailova et al, 2011;Nagy-Deri et al, 2011).…”
Section: Resultssupporting
confidence: 61%
“…To our knowledge, relatively few studies have been carried out to characterize chloroplast structure and chlorophyll synthesis of resurrection Ramonda plant species and Haberlea rhodopensis. Most published data describe the size, shape, and number of chloroplasts or chloroplast structure in the palisade and spongy parenchyma layers of H. rhodopensis leaves during drought (Georgieva et al, 2010;Nagy-Deri et al, 2011) or chlorophyll content and chlorophyllase activity during the dehydration and rehydration cycles of R. serbica and R. nathaliae (Drazic et al, 1999;Gashi et al, 2013). The aim of this study is to determine the importance of early steps of chlorophyll biosynthesis during the dehydration and rehydration cycles of resurrection plants, including the response of ALA-D activity to water deficit and differences between R. nathaliae and R. serbica with respect to contents of aminolevulinic acid (ALA) and chlorophyll content during this period.…”
Section: Introductionmentioning
confidence: 99%